Biofiltration of Volatile organic compounds Using Chir Pine Cone Nuts Inoculated with Pseudomonas putida - Kumar, Sanjeev; Kumar, Divya (Ecological Questions, 2023)
Volatile organic compounds (VOCs) and hazardous air pollutants (HAPs) are the major pollutants in industrial and agricultural emissions. This study targets the efficiency and applicability of biofiltration to remove methanol and n-hexane, two common air pollutants, using Chir pine cone nuts as filter media and Pseudomonas putida as the inoculant. The designed biofilter was operated between 25-35°C, with an airflow rate of 0.35 m3 h-1 and nutrient supply of 1-2 L Day-1. From a 60-day operating period, methanol's removal efficiency was higher than n-hexane, with a maximum removal efficiency of 93.91% achieved at an inlet loading rate of 101.39 g m-3h-1 for methanol and 87.96% at 398.46 g m-3h-1 for n-hexane. The effects of varying loading rates on the elimination capacity for both pollutants were also studied. In addition, the temperature profile of the biofilter, microbial analysis, and the BOD concentration of leachate was also studied during the operation period. The findings offer insights into the potential use of Chir pine nuts as filter media for the biodegradation of methanol and n-hexane and provide a foundation for future research to optimize the biofilter system's design and operation to increase its removal efficiency of other contaminants.